Pictorial essay: Breast USG - Shah, Geeta; Jankharia, Bijal (Indian Journal of Radiology and Imaging, 2010)
USG of the breast is now an established modality. It is used in the characterisation of focal breast lesions as well as in the primary evaluation of mammographically dense breasts. It helps guide biopsies as well. We present a pictorial essay on the role of USG in various breast pathologies
Keywords: Breast; ultrasound; mammography